Processing and Quality Aspects of Value Added Indigenous Processed Camel Meat Product (Nyirinyiri) - Stephen W. Kisembe; Patrick S. Muliro; Joseph W. Matofari; Bockline O. Bebe (Research Perspectives of Microbiology and Biotechnology Vol. 8, 2024)
This book chapter discusses the processing and quality aspects of traditionally processed camel meat (Nyirinyiri) among the pastoral communities in Eastern Africa (Kenya). It outlines the principal technology involved in the processing and preservation, providing the generalized aspects of their indigenous knowledge practice. The camel meat product being discussed is one that is sun-dried, deep-fried, and preserved in fat. Nyirinyiri has been proven to confer certain nutritional and therapeutic benefits to consumers. Camel processed meat forms an important food component in the diet of pastoral households because it is a major source of protein containing high biological value as well as micronutrients. It is considered a functional food because it cures and remedies many ailments as discussed under therapeutic benefits. The quality and safety aspect of Nyirinyiri was discussed in a study whose findings indicated that the product was safe for consumption. Safety during processing can be assured by the adoption of strict sanitary guidelines and procedures during processing and preservation.